Cross Channel Integration Dalam Meningkatkan Retensi Pelanggan Pada Industri Ritel - Ronny Samsul Bahri; Laura Lahindah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
In today's challenge, retailers are starting to use an omnichannel strategy that utilizes Cross-Channel Integration (CCI) to coordinate various retail channels and retain customers. CCI is designed to improve customer access and interaction with online and offline channels during the shopping process. This strategy is done to improve customer experience and increase Customers Retention (CR) which is the core goal of CCI. This research is a causal- comparative study to find out whether there is an influence between Cross Channel Integration on Customer Retention. The survey was conducted on 83 consumers who have used online and offline retail channels such as IKEA and Ace Hardware. By distributing questionnaires online, it was found that CCI had a positive effect on CR. This proves that the omnichannel retail strategy by utilizing CCI is one of the goals in increasing retail consumer retention in shopping